Understanding characters: a cognitive stylistics of the communication of experience - Sanchez-Davies, Jennifer (2017)
Over the last decade, research in characterisation has proliferated in (cognitive) stylistics, with investigations exploring the different avenues concerning the conceptualisation and presentation of fictional characters. There is a wealth of theoretical work on the definition of character, yet a weakness lies in the lack of unification of this information into a systematic method of analysis that can holistically represent characters as the unique individuals they are. This thesis sets to fill this hiatus by developing an adaptable, strategic method of analysis to comprehensively represent characters.